Cervical spine fracture in a patient with ankylosing spondylitis causing a C2-T9 spinal epidural hematoma- Treatment resulted in a rapid and complete recovery from tetraplegia: Case report and literature review - Wong, Albert; Yu, Denis (Asian Journal of Neurosurgery, 2015)
Full recovery from tetraplegia is uncommon in cervical spine injury. This has not being reported for cervical spine fracture in a patient with ankylosing spondylitis causing spinal epidural hematoma. We report on a case of cervical spine fracture in a patient with ankylosing spondylitis who came with tetraplegia. He underwent a two stage fixation and fusion. He had a complete recovery. Two hours after the operation he regained full strength in all the limbs while in the Intensive Care Unit. He went back to full employment. There are only two other reports in the literature where patients with ankylosing spondylitis and extradural hematoma who underwent treatment within 12 h and recovered completely from tetraparesis and paraplegia respectively. Patient with ankylosing spondylitis has a higher incidence of spinal fracture and extradural hematoma. Good outcome can be achieved by early diagnosis and treatment. This can ensure not only a stable spine, but also a rapid and complete recovery in a tetraplegic patient.
Keywords: Ankylosing spondylitis; complete recovery; fracture; tetraplegia